Vaccine-associated paralytic Poliomyelitis: a case report of domiciliary transmission - Paz, José A.; Vallada, Marcelo G.; Marques, Silvia N. C. H.; Casella, Erasmo B.; Marques, Heloisa H. S.; Marques-Dias, Maria J. (Revista do Hospital das Clínicas, 2000)
Poliomyelitis associated with live strain vaccine is defined as the paralytic form of the acute anterior poliomyelitis related to the vaccine strain. Since these strains behave similarly to the wild-type virus, we can differentiate, epidemiologically, two types of vaccine-associated poliomyelitis: cases in which the patient was vaccinated and cases in which the patient had had contact with vaccinated individuals. We herein present the case of an unvaccinated child, with a clinical picture of an acute anterior poliomyelitis associated with the live strain vaccine, whose brother received the Sabin vaccine 20 days before the onset of the symptoms. Vaccine strain of the type 3 poliovirus was isolated in fecal culture and a presented mutation in nucleotide 472 (C;®;U) in the 5' non-coding region, which is strongly related to the higher strain virulence.